2020
DOI: 10.1038/s41598-020-57945-4
|View full text |Cite|
|
Sign up to set email alerts
|

Onecut-dependent Nkx6.2 transcription factor expression is required for proper formation and activity of spinal locomotor circuits

Abstract: In the developing spinal cord, Onecut transcription factors control the diversification of motor neurons into distinct neuronal subsets by ensuring the maintenance of Isl1 expression during differentiation. However, other genes downstream of the Onecut proteins and involved in motor neuron diversification have remained unidentified. In the present study, we generated conditional mutant embryos carrying specific inactivation of Onecut genes in the developing motor neurons, performed RnA-sequencing to identify f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…Members of the Onecut family of TFs have so far been identified as critical for the development of hepatocytes, endocrine cells of the pancreas and the gastrointestinal tract, and the spinal cord 13–20 . Nevertheless, their localization in the brain remains incomplete particularly because of the lack of genetic tools to faithfully chart the distribution of neurons expressing Onecut paralogs, and to interrogate their connectivity to infer functions.…”
Section: Resultsmentioning
confidence: 99%
“…Members of the Onecut family of TFs have so far been identified as critical for the development of hepatocytes, endocrine cells of the pancreas and the gastrointestinal tract, and the spinal cord 13–20 . Nevertheless, their localization in the brain remains incomplete particularly because of the lack of genetic tools to faithfully chart the distribution of neurons expressing Onecut paralogs, and to interrogate their connectivity to infer functions.…”
Section: Resultsmentioning
confidence: 99%
“…Onecut2 encodes a member of a family of transcription factors that function as transcriptional activators controlling cell differentiation and survival, as well as oxidative defense signaling, and that have only been recently proposed as regulators of neuronal differentiation [ 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 ]. Showing a consistent increased expression of this TF in CGNs during NF-mediated rescue, our results support the importance of Onecut2 for neuronal survival ( Figure 1 and Figure 3 ) [ 43 ].…”
Section: Cracking the Transcriptional Regulatory Programs Of Neuronal...mentioning
confidence: 99%
“…According with the anti-apoptotic, anti-oxidative and anti-inflammatory effects of this TF, we observed its increased expression following NF-induced neuronal apoptotic rescue ( Figure 1 and Figure 3 ) [ 43 ]. From a clinical point of view, Twist2 is upregulated in a variety of cancers, including glioma and neuroblastoma [ 181 ]. In addition, Twist2 dysfunctions are associated with human pathological conditions characterized by oxidative stress-induced neuronal death, supporting its potential role as therapeutical target for cancer and neurological diseases [ 199 , 200 , 200 , 201 , 202 , 203 ].…”
Section: Cracking the Transcriptional Regulatory Programs Of Neuronal...mentioning
confidence: 99%
“…In mice, overexpression of miR-9 induces neuronal differentiation by inhibiting the nuclear receptor [ 134 , 135 ], suggesting that miR-9 plays a role in fine-tuning the process of specification of MN subtype identity. Other studies showed that ISL1 expression by Onecut transcription factors (OC1) was important to generate LMC MNs [ 133 , 156 , 157 ]. Studies showed that miR-9 and OC1 are in mutually exclusive patterns in the embryonic spinal cord and miR-9 efficiently represses OC1 expression, demonstrating that regulation of OC1 by miR-9 is a crucial step in the specification of spinal MNs.…”
Section: Generation Of Hipsc-derived Mnsmentioning
confidence: 99%